How to make herbal medicine available in health facilities in Indonesia? - Destiwati, Rita (BKM Public Health and Community Medicine, 2021)
Health facilities are the government’s responsibility in Indonesia following the law number 36 of 2009. This aims to improve the highest health status for the public. Herbal alternative medicine is not a new treatment globally, but this plant-based medicine has existed for centuries, including in Indonesia. The habit of drinking herbal medicine to maintain health or cure disease is usually carried out by people in Indonesia, both rural and urban. The purpose of this study was to find out whether it is possible for health insurance in Indonesia to accept alternative herbal treatments in primary care facilities. This study uses qualitative research methods by conducting interviews, observations, and literature studies. Informants in this study were patients who had undergone medical surgery and patients who had consumed and performed alternative herbal treatments: health facility policymakers and doctors. The results showed differences in the acceptance of services for the healers (doctors and therapists). Health communication, in this case, can provide alternative solutions so that the comfort of patients is free to choose who they seek treatment with mild side effects. The patients prefer to go to alternative herbal medicine, not because of the medicine, but because the established communication is very intense and cooperative between the two. So the government health facility regulations should have started reviewing policies so that alternative herbal treatments can be included in government-owned health facilities or health insurance that has received permission from the government. Fasilitas kesehatan merupakan tanggung jawab pemerintah di Indonesia, ini sudah diatur secara undang-undang nomor 36 tahun 2009. Ini bertujuan untuk meningkatkan derajat kesehatan yang setinggi-tinggi bagi masyarakat. Pengobatan alternative herbal bukan pengobatan baru di dunia, tapi pengobatan yang berbahan dasar tumbuh-tumbuhan ini sudah ada berabad-abad yang lalu termasuk di Indonesia. Kebiasaan minum jamu untuk menjaga kesehatan atau penyembuhan penyakit biasa dilakukan oleh masyarakat di Indonesia baik desa atau kota. Tujuan dari penelitian ini untuk mengetahui mungkinkah jaminan kesehatan di Indonesia bisa menerima pengobatan alternative herbal masuk dalam fasilitas layanan primer. Penelitian ini menggunakan metode penelitian kualitatif dengan melakukan wawancara, observasi dan studi literature. Informan pada penelitian ini para pasien yang pernah melakukan tindakan operasi secara medis juga para pasien yang sudah mengkonsumsi dan melakukan pengobatan alternative herbal. Para pembuat kebijakan fasilitas kesehatan dan dokter. Hasil penelitian menunjukkan kalau adanya perbedaan dalam penerimaan layanan bagi para pengobat (dokter dan Therapist). Komunikasi kesehatan dalam hal ini bisa memberikan solusi alternative sehingga kenyamanan para pasien bebas untuk memilih pada siapa mereka berobat dengan efek samping yang ringan. Para pasien lebih senang berobat ke pengobatan alternative herbal bukan karena obatnya tapi komunikasi yang terjalin sangat intens dan kooperatif diantara keduanya. Jadi seharusnya dalam aturan fasilitas kesehatan pemerintah sudah mulai mengkaji kebijakan agar pengobatan alternative herbal bisa masuk dalam fasilitas kesehatan milik pemerintah ataupun Asuransi kesehatan yang sudah dapat izin dari pemerintah.